Fertility Preservation in Women With Endometriosis - Natalia C Llarena; Tommaso Falcone; Rebecca L Flyckt (SAGE Publishing, 2019)
Infertility affects 30% to 50% of women with endometriosis. Women with endometriosis are at risk of decreased ovarian reserve, both because of the pathophysiology of the disease and iatrogenic injury resulting from surgical intervention. Fertility preservation must occur at multiple levels, including careful selection of surgical candidates, avoidance of repeat procedures, and meticulous surgical technique. Fertility preservation with oocyte or ovarian tissue cryopreservation may be considered on an individual basis for women with endometriosis, particularly those at risk of bilateral ovarian injury, such as women with bilateral endometriomas.